Modal Analysis Investigation of Kris Collision Utilizing Finite Element Method - Stesal Waradana; Ubaidillah Ubaidillah; Aditya Rio Prabowo; Bhre Wangsa Lenggana; Rahmawati Rahmawati; Monsak Pimsarn (Evergreen, 2024)
Scientific research on krises is still quite limited.Early days of kris, the dissemination of knowledge and technology about kris was done orally through a teacher (empu) and a diligent student who was trusted by the empu.Thus, learning and research on kris is more challenging and makes the secrets of the art of kris more difficult to uncover.In this research, we will study the natural frequency and impact stress of various krises simulated with Ansys software as one of the applications to analyze finite elements.The output of the research is expected that the unique shape of the kris influences the resulting vibration characteristics.The number of Luk variations on the kris affects the natural frequency, stress, and total deformation produced.In the same mode, different results are obtained for each variation of Luk krises, such as in mode 4, Luk 3, Luk 7, and Luk 13 of kris have natural frequency values of 976.73 Hz, 750.78 Hz, and 626.58 Hz, respectively.Thus, the natural frequency, impact stress, and total deformation of each kris variation have different results due to the number of Luk on the kris.The results of total deformation during impact show that the kris variation model's performance also decreases or increases depending on the application.
Keywords: Fluid Dynamics Simulations and Interactions; High-Velocity Impact and Material Behavior; Dynamics and Control of Mechanical Systems